2015 International Conference on Industrial Engineering and Systems Management (IESM) 2015
DOI: 10.1109/iesm.2015.7380255
|View full text |Cite
|
Sign up to set email alerts
|

Cost and benefit analysis of supplier risk mitigation in an aerospace Supply chain

Abstract: This version is available at https://strathprints.strath.ac.uk/55539/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(38 reference statements)
0
3
0
1
Order By: Relevance
“…The results show that this method can reduce the possibility of potential failure and improve the risk level when failure occurs. Qazi et al (2016) proposed a new approach to risk assessment by simultaneously considering complexity. They found that there are interdependencies among complexity drivers, risks, and goals, and their approach is also able to prioritize complexity drivers, risks, and strategies.…”
Section: Evidence Theorymentioning
confidence: 99%
“…The results show that this method can reduce the possibility of potential failure and improve the risk level when failure occurs. Qazi et al (2016) proposed a new approach to risk assessment by simultaneously considering complexity. They found that there are interdependencies among complexity drivers, risks, and goals, and their approach is also able to prioritize complexity drivers, risks, and strategies.…”
Section: Evidence Theorymentioning
confidence: 99%
“…The results show that this method can reduce the possibility of potential failure and improve the risk level when failure occurs. Qazi et al (2016) proposed a new approach to risk assessment by simultaneously considering complexity. They found that there are interdependencies among complexity drivers, risks, and goals, and their approach is also able to prioritize among complexity drivers, risks, and strategies.…”
Section: Evidence Theorymentioning
confidence: 99%
“…In these scenarios, the priorities are based on the cost of the whole product life cycle and are connected with the correction actions which are to be planned. Qazi et al [9] proposed a method of evaluating different mitigation strategies through cost and benefit analysis. Chen and Zhang [10] integrated the technique of FMEA and analysis of equipment maintenance cost to optimise the life cycle cost of equipments’ decision in order to sustain and promote the firms’ competitive capability.…”
Section: Literature Reviewmentioning
confidence: 99%